2021
DOI: 10.1111/anu.13249
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of superworm, Zophobas morio , meal as a partial fishmeal replacer in fingerling rainbow trout, Oncorhynchus mykiss , diet: growth performance, amino acid profile, proteolytic enzymes activity and pigmentation

Abstract: To characterize the effects of a defatted superworm meal (SWM) on the zootechnical performance and nutrient utilization of fingerling rainbow trout, we provided five practical diets with 0 (control), 10, 20, 30 and 40% SWM to substitute fishmeal. Fingerlings (N = 225; 9.9 ± 0.5 g) were randomly allocated over five treatments in triplicate. After eight weeks, the replacement of fishmeal with SWM up to 110 g/kg did not induce significant variations in the final weight and weight gain rate compared to the control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Therefore, the crude lipid content increased progressively with the increase of the level of fish meal replaced by the Tubiechong by-product. Similar results were shown in previous studies [ 22 , 34 ]. The above results indicated that partial replacement of fish meal by the Tubiechong by-product positively affected the growth performance of largemouth bass to some extent.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, the crude lipid content increased progressively with the increase of the level of fish meal replaced by the Tubiechong by-product. Similar results were shown in previous studies [ 22 , 34 ]. The above results indicated that partial replacement of fish meal by the Tubiechong by-product positively affected the growth performance of largemouth bass to some extent.…”
Section: Discussionsupporting
confidence: 93%
“…Chemello et al also found that the growth and morphometric parameters of rainbow trout ( Oncorhynchus mykiss ) were not affected by defatted yellow mealworm ( Tenebrio molitor ) dietary inclusion [ 21 ]. Similarly, partially or entirely replacing fish meal with cricket ( Gryllus bimaculatus ) or superworm ( Zophobas morio ) did not lead to negative effects on the growth of olive flounder ( Paralichthys olivaceus ) or rainbow trout ( Oncorhynchus mykiss ), respectively [ 22 , 23 ]. In the study, when the substitution level reached 40%, the growth performance decreased slightly.…”
Section: Discussionmentioning
confidence: 99%
“…At the end of the feeding period, the feeding was stopped for 24 h, the fish anaesthetised using clove powder (150 mg/L; Hosseini Shekarabi et al, 2021) and growth and nutritional indices were calculated using the following equations:Weight gain0.25em)(WGgoodbreak=Final weightInitial weightleftSpecific growth rate0.25em)(SGR,%/dayleftgoodbreak=100goodbreak×][)(ln0.25emfinal weightln0.25eminitial weightDays Feed conversion ratio0.25em)(FCRgoodbreak=Food consumedFinal weightInitial weightProtein efficiency ratio0.25em)(PERgoodbreak=WGTotal protein intakenormalg0.25emSurvival rate0.25em)(,SR%goodbreak=)(Number of alive fishTotal number of fishgoodbreak×100…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate serum immune parameters, three fish were anaesthetised from each tank using clove powder (150 mg/L; Hosseini Shekarabi et al, 2021). Blood samples were taken from the caudal peduncle using a 2 ml syringe.…”
Section: Methodsmentioning
confidence: 99%
“…All components were incorporated, and then, sunflower oil, Kilka fish oil and lecithin were added to the blend. Finally, lukewarm water was poured and mixed for 25 min to produce a stiff paste (Hosseini Shekarabi et al, 2021). The dough was pressure-pelleted by a meat grinder (Pars Khazar, Tehran, Iran) with a 1-mm stainless steel grinding disc.…”
Section: Experimental Diets Preparationmentioning
confidence: 99%